Synthesis, crystal structure, and luminescence properties of RbCaF3:Eu3+ orange-red emitting phosphors for white light emitting diodes. Issue 7 (1st April 2023) - Raja, Arumugam; Annadurai, G.; Sivasubramani, V.; Ramachandran, K.; Kamesh, R.; Govindan, V.; Vijayakumar, P.; Siva, V.; Ramasamy, P.
Abstract: A series of novel orange-red emitting RbCaF3 :0.05Eu 3+ phosphors were synthesized by solid-state reaction technique. Phase formation and crystal structure of RbCaF3 were investigated through powder X-ray diffraction patterns and Rietveld refinement. Through X-ray photoemission spectroscopy, their composition and nature of oxidation states were determined. These fluoroperovskite phosphors are efficiently excited by near ultraviolet (n-UV-394 nm) and a corresponding sharp emission peak is exhibited at 590 nm. This peak can be attributed to the 5 D0 → 7 F1 transition of the magnetic dipole. A concentration quenching effect can be observed with increasing Eu 3+ ion concentration. The Commision Internationale del'Eclairage (CIE) chromaticity coordinates (x = 0.5764, y = 0.4277) of the RbCaF3 : 0.05Eu 3+ phosphors excited at 394 nm. Thermally stimulated luminescence (TSL) was carried out and analyzed for the trap depth (E) and frequency factor values. The above results indicate that the RbCaF3 :0.05Eu 3+ can be a potential orange-red emitting phosphor for white light emitting diodes.